The contribution of CT scan examination in forensic anthropology: A systematic review - Alias A.; Ibrahim A.N.; Shafie M.S.; Abu Bakar S.N.; Mohd Fadzilah F.; Mohd Nor F. (Japan International Cultural Exchange Foundation, 2024)
Indexed by SCOPUS